2021
DOI: 10.3389/fcvm.2021.612215
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Differences in Protein Expression in Sarcomere Mutation-Positive Hypertrophic Cardiomyopathy

Abstract: Background: Sex-differences in clinical presentation contribute to the phenotypic heterogeneity of hypertrophic cardiomyopathy (HCM) patients. While disease prevalence is higher in men, women present with more severe diastolic dysfunction and worse survival. Until today, little is known about the cellular differences underlying sex-differences in clinical presentation.Methods: To define sex-differences at the protein level, we performed a proteomic analysis in cardiac tissue obtained during myectomy surgery to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Recent studies also suggest differences in the proteome of male and female cardiomyopathic hearts at early and advanced disease stages. 91 , 92 For example, proteomics and functional studies have identified tubulins as potential treatment targets for HCM. 93 , 94 , 95 It has been hypothesized that the higher tubulin levels found in female patients may contribute to their more advanced diastolic dysfunction compared with men.…”
Section: Sex‐specific Pathomechanisms and Cardiac Remodelingmentioning
confidence: 99%
“…Recent studies also suggest differences in the proteome of male and female cardiomyopathic hearts at early and advanced disease stages. 91 , 92 For example, proteomics and functional studies have identified tubulins as potential treatment targets for HCM. 93 , 94 , 95 It has been hypothesized that the higher tubulin levels found in female patients may contribute to their more advanced diastolic dysfunction compared with men.…”
Section: Sex‐specific Pathomechanisms and Cardiac Remodelingmentioning
confidence: 99%
“…While genetic cellular and animal models have yielded highly valuable insights into disease pathogenesis, these models do not always faithfully recapitulate features of human HCM. A number of studies using septal myectomy specimens from patients with HCM have identified increased myofilament calcium sensitivity, 6 increased actomyosin ATPase activity, 7 calcium dyshomeostasis, 8 protein quality control abnormalities, 9 and multiple differences in protein abundance [10][11][12] when compared with control hearts. While some disease-related aberrations are more pronounced, or in some cases specific to sarcomeric HCM, many seem to be genotype-independent and thus may represent shared downstream pathways related to secondary cardiac remodeling.…”
mentioning
confidence: 99%
“…The first explanation is supported by studies that observed a later disease penetrance in women compared with men with the same causing genotype 5 6 27. In addition, Schuldt et al observed that cardiac tissue samples from women undergoing SM had higher levels of heat shock proteins and that sex hormone-associated transcription factors lead to variations in protein expression contributing to the delayed disease onset 28. Other researchers found a higher LV wall thickness depending on variations in the androgen and oestrogen receptor genes 29.…”
Section: Discussionmentioning
confidence: 94%